A Case Report of Primary Malignant Pulmonary Melanoma - Balci, Akin Eraslan; Kilic, Murat; Calik, Ilknur; Murat, Ayse (Aves, 2022)
We operated on primary malignant melanoma of the lung, attaching the pericardium, diaphragm, and parietal pleura. A 48-year-old female was admitted to our hospital because of persistent dyspnea and cough. A preoperative computed tomography of the chest revealed 3 lesions in the right lung and a mass on the diaphragm between the right lung's lower lobe and heart. A middle lobectomy was performed. The mass on the diaphragm had invaded the diaphragm and pericardium strictly. With a pericardiectomy and a diaphragmatic resection, the mass was removed in an en-bloc manner. Adjuvant chemotherapy was started 1 month after surgery and consisted of 5 days course of iv injection of cisplatin (90 mg/kg). The follow-up period was 5 years and uneventful. For primary pulmonary melanoma, even if it has intrapulmonary metastases, surgery and adjuvant chemotherapy can provide uneventful survival for more than 5 years.
Keywords: malign melanom; lung resection